The Effect of E-Procurement Implementation on The Quality of Selection of Goods and Services Providers Through the Tender Method at The Procurement Service Office - Dani Rudiana; Herwan Abdul Muhyi; Iwan Sukoco (Business and Applied Management Journal, 2026)
This study aims to analyze the effect of e-procurement implementation on the quality of selection of goods and services providers through the tender method at the Procurement Services Office at the University. This research is motivated by the increasing demand for transparency, efficiency, and accountability in public procurement, particularly within higher education institutions. This research uses a quantitative approach, with data collected through questionnaires distributed to providers directly involved in the tender process. Data analysis was conducted using statistical techniques to examine the relationship between e-procurement implementation and the quality of provider selection, measured through indicators of transparency, fairness, efficiency, and compliance with procurement regulations. The results indicate that e-procurement implementation has a positive and significant effect on the quality of provider selection through the tender method. These findings demonstrate that e-procurement enhances transparency, minimizes procedural deviations, and improves the quality of decision-making in provider selection. This study provides empirical contributions to the field of public sector procurement, particularly in the context of higher education institutions.